Komunikasi Antara Orang Tua dan Siswa dalam Meningkatkan Motivasi Belajar - Sintiya Mohafifah; Ahmadi Ahmadi (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2023)
This study focuses on the communication between parents and students to enhance students' motivation in studying Islamic religious education. Parental communication plays a crucial role in providing motivation, which is considered a key factor in improving students' learning outcomes. A qualitative approach was employed to investigate this issue, utilizing interviews and observations as the primary research methods. The research was conducted at MI Al-Ihsan 1 B, located in Jaddung village, Pragaan sub-district, Sumenep district. The study participants consisted of five student guardians, five students, and two teachers from MI Al-Ihsan 1 B. To ensure data validity, the researcher employed the triangulation method. The communication between parents and children that enhances motivation to learn Islamic religious education occurs through face-to-face interactions. Verbal communication, both oral and written, plays a significant role in this process.